(untitled) (Global Journal of Human-Social Science, 2020)
The myth of Medea1has become familiar in the Greek literature since Homer’s time. He told the story about the trip of the Argonauts guided by Jason. The mythical narrative has different versions that survived in various informative supports such as the texts of the dramatic poets and the images of the Greek vases. In this essay, we propose to analyse the remote information and reference of the action of the myth of Medea through the Greek vases. We selected to research about the episode that has been known as Pelíades. We may infer there are two versions about Medea and Pelias, in the most remote of them the priestess of Hekate belongs to the seventh century and, in this period, Medea has the ability to cure and rejuvenate an old person. This information shows the mythological narrative of Pelias and Medea is very ancient.